Flat output and switchable fiber laser using AWG and broadband FBG - Zulkifli, Mohd Zamani; Tamchek, Nizam; Latif, Amirah Abdul; Harun, Sulaiman Wadi; Ahmad, Harith (Elsevier, 2009)
The switchable multiwavelength fiber laser (SMWLSs) using AWG and broadband FBG with tuning range 11.7 nm and 0.75 nm spacing are demonstrated. The switchable lasers for every channel shows flatness output power with variation 3.7 dBm and peak power around -6.1 dBm. The side mode suppression ratio (SMSR) of the laser is significantly improved for every channel when using broadband FBG. The improvement is about 27.7 dBm. The laser for every channel also shows the good stability within the 2 h operation.